2022
DOI: 10.18485/aeletters.2022.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Modes for the Production of Micro Range Metal Powders

Abstract: This paper presents the results of working out the modes of obtaining micro range powders according to the developed method. It is based on the navigation on the material of the vortex plasma flows of heterogeneous plasma and synchronized high-frequency impact on the electrode. The formation of powders is derived from individual particles heated and accelerated using a high-temperature gas jet -plasma. It is obtained in a special original plasma generator by blowing the plasma-forming inert gas into an electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…It is also remarked that the majority of particles exhibit a flaked-like morphology with a length of about 2× higher than the corresponding widths. It is also interestingly verified that the bimodal distributions are characterized, as also reported in other studies with Al powders obtained in similar operational conditions [25][26][27][28].…”
Section: Powder Size Distribution and Microstructuresupporting
confidence: 87%
See 1 more Smart Citation
“…It is also remarked that the majority of particles exhibit a flaked-like morphology with a length of about 2× higher than the corresponding widths. It is also interestingly verified that the bimodal distributions are characterized, as also reported in other studies with Al powders obtained in similar operational conditions [25][26][27][28].…”
Section: Powder Size Distribution and Microstructuresupporting
confidence: 87%
“…Kuznetsov et al [28] have recently reported that distinct technologies for the production of metal powders are developed, e.g., gas, water spraying, centrifugal spraying, plasma spraying, mechanical grinding and doping, solid phase recovery, electrolytic and various chemical processes. From these, distinctive morphologies, shapes and sizes are attained.…”
Section: Introductionmentioning
confidence: 99%